Unification of Collision of Law in International Trade on the example of the Hague Conference on PIL (International relations and international law Journal, 2016)
This article discusses the prospects of participation ofthe Republic of Kazakhstan in Hague Conference on PrivateInternational Law on the unification of collision law in theinternational trade.The article analyzes some conventions on international trade. Theappropriate conclusions based on the opinions of scientists andexperts in this field have been made. First, all issues presented in the form of gaps or spaces in conventions should be the subject to directnegotiations in the course of the activities of Hague Conference, andhave a comprehensive feature, be transparent and taken undersimplified procedure. Secondly, one should not underestimate the value of conventionsthat do not become active due to various reasons and having apositive impact on the development and improvement of nationallegislation and practice in the field of private international law. Thirdly, Kazakhstan has to reconsider its attitude to HagueConference, having become its full member and aiming at providingconstructive and fruitful cooperation with both the organization itselfand its member states.
Keywords: Hague Conference on Private International Law; Hague Conventions; unification; collision norms; international trade; international private law; integration